THE EFFECT OF PROPANOLOL ON C-REACTIVE PROTEIN IN PATIENTS WITH SEVERE BURNS AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Muhammad Aulia U H; Iswinarno Doso Saputro; Magda Rosalina Hutagalung (Jurnal Rekonstruksi dan Estetik)
Highlights: